The Epistemological Status of Charisma in Historical Macrosociology - D. V. Kataev; V. O. Kalinina (Социология власти)
The uncertain epistemological status of charisma is largely due to its polysemy and polymorphism. Max Weber thematizes it in a variety of contexts and meanings — distinguishing between magical, religious charisma and the charisma of reason, highlighting the trajectories of routinization and objectification of charisma, typologizing different types of prophecies. In turn, the multiple (re)actualizations of this "brilliant concept” [Rose] as reinforcements of their own theories in the form of varieties of symbolic capital, resonance, the everyday, the re-personalized, or the risky charisma lead to either semantic compression or the blurring of meaning, both within sociological theory and in interdisciplinary discourse. To define the scientific content of charisma, the authors propose to thematize it in historical macrosociology. The key question is addressed to the interdisciplinary connections in Weber's intellectual heritage — is the category "charisma” attributable to Weber the historian or Weber the sociologist?The clarification of the epistemological status of charisma, expressed in its dual character (phenomenon vs. ideal type), becomes possible thanks to the discussion of a corpus of the classic texts by two prominent German Weberologists — W. Schluchter and F. Tenbruck. In its turn, the reconstruction and systematization of approaches of Weberian historical macrosociology allows us to clarify the boundaries and possibilities of the category's application. Thus, the evolutionary-theoretical perspective defines the heuristic potential of charisma in terms of reflecting the dynamics of cultural and value orientations in the process of emergence and consolidation of social order and institutional structures. The comparative-historical approach, in turn, defines the relationship between the analytical and empirical levels of Weber's sociology through the "immersion” of an ideal-typical construct in a real historical narrative. In this way, historical macrosociology overcomes the most valid criticisms (S. Turner) of the category's failure, heterogeneity, and its residual character.